2010
DOI: 10.1002/tox.20544
|View full text |Cite
|
Sign up to set email alerts
|

Trace metal dynamics in zooplankton from the Bay of Bengal during summer monsoon

Abstract: Trace metal (Fe, Co, Ni, Cu, Zn, Cd, and Pb) concentrations in zooplankton from the mixed layer were investigated at 8 coastal and 20 offshore stations in the western Bay of Bengal during the summer monsoon of 2003. The ecotoxicological importance of trace metal uptake was apparent within the Bay of Bengal zooplankton. There was a distinct spatial heterogeneity of metals, with highest concentrations in the upwelling zones of the southeast coast, moderate concentrations in the cyclonic eddy of the northeast coa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
5
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(6 citation statements)
references
References 29 publications
1
5
0
Order By: Relevance
“…However, at site 4, almost all of the dissolved concentrations of the tested metals were above the Tamil Nadu Government Pollution Control Board recommended values for inland, marine and coastal waters (TNPCB, 2000). The concentrations of different toxic metals observed during this study were comparable to earlier reports for the Ennore estuary (Jayaprakash et al, 2005(Jayaprakash et al, , 2008 and from the southeast coast of India (Rejomon et al, 2008(Rejomon et al, , 2010. Despite the highest concentration of Zn in all four components (water, particulate, sediment and zooplankton), statistical analysis revealed Zn does not pose greater genotoxic threat to the tested zooplankton species in comparison to other toxic metals (Pb, Ni, Cu, Cr and Co).…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…However, at site 4, almost all of the dissolved concentrations of the tested metals were above the Tamil Nadu Government Pollution Control Board recommended values for inland, marine and coastal waters (TNPCB, 2000). The concentrations of different toxic metals observed during this study were comparable to earlier reports for the Ennore estuary (Jayaprakash et al, 2005(Jayaprakash et al, , 2008 and from the southeast coast of India (Rejomon et al, 2008(Rejomon et al, , 2010. Despite the highest concentration of Zn in all four components (water, particulate, sediment and zooplankton), statistical analysis revealed Zn does not pose greater genotoxic threat to the tested zooplankton species in comparison to other toxic metals (Pb, Ni, Cu, Cr and Co).…”
Section: Discussionsupporting
confidence: 88%
“…It is reported that fish feeding on metal contaminated zooplankton have biomagnified metal residues in their tissue by a factor of two (Sandholm et al, 1973;Zhou et al, 2008). In several environmental monitoring studies, zooplankton are widely used as potential biomarkers for metal contamination in the marine environment (Pempkowiak et al, 2006;Kahle and Zauke, 2002;Rejomon et al, 2010;Severini et al, 2009). However, most of these studies have focused only on the bioaccumulation potential of these organisms and studies on genotoxic impact of trace/heavy metal on zooplankton are very rare (Ternjej et al, 2009).…”
Section: Introductionmentioning
confidence: 96%
“…Phytoplankton incorporate TMs through adsorption onto the cell surface and intracellularly through the passive and active uptake of dissolved elements (González-Dávila, 1995;Ho et al, 2007;Sakata et al, 2012). Mesozooplankton take up TMs through these mechanisms and the ingestion of polluted prey (Rejomon et al, 2010;Wright et al, 2010). Therefore, the relationships between the water TM concentrations and those observed in zooplankton could indicate direct absorption/adsorption.…”
Section: Bioaccumulationmentioning
confidence: 99%
“…In turn, the cycling of these elements is also influenced through biological activity. Phytoplankton accumulate TMs and transfer these particles up the food web via zooplankton (Gozález-Dávila, 1995;Rejomon et al, 2010). When ingested by zooplankton, a portion of the TMs is returned to the water through excretion and the production of fecal pellets (Lee and Fisher, 1992;Wang and Fisher, 1998).…”
Section: Introductionmentioning
confidence: 99%
“…Hence, the bioaccumulation of metals in zooplankton depends upon bioavailability, the amount of dissolved metal uptake, the physiological efficiency of the organism to excrete metals, as well as on the feeding rate and prey availability (Rainbow, 1997). Differences in the bioaccumulation factors for elements like Co, Ni, Cu, Zn and Cd compared with the essential element Fe and non-essential element Pb, might be related to different physiology of copepods feeding in coastal and offshore waters (Rejomon et al, 2010). Wide fluctuation in the concentration of metals in different groups of zooplankton was observed.…”
mentioning
confidence: 99%